APPLICATION OF DEMONSTRATION METHODS TO IMPROVE STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING ENERGY SOURCES MATERIAL - Rosmaya, Andriyanti; Garini, Fitriyani Via Ardya; Ruqoyyah, Siti (IKIP Siliwangi, 2018)
The main problem of this research is low second grade students learning outcomes of Ciampel Elementary School Padalarang subdistrict Bandung Barat Regency in science subject energy source material. Class Action Research has been carried out which aim to improve student learning outcomes in science of energy resource material through the application method demonstration method in the second grade of Ciampel Elementary School. This research was carried out in two cycles, each cycle consisted of 4 stages. Namely : Planing, action, observation and reflection with the number of 30 students consisting of 10 boys and 20 girls. Trought out the last result of evaluation in the first cycle is obtained mastery of clasical learning amount 63.33% and the average value is 67.66. The result of the last evaluation of the second cycle is obtained mastery of classical learning amount is about 80% and the average value is 72,8. It can be concluded that the application of demonstration method is able to increase in science subject about energy resource material in second grade Ciampel Elementary School.